2020
DOI: 10.1016/j.cpr.2020.101931
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of online psychological and psychoeducational interventions to prevent depression: Systematic review and meta-analysis of randomized controlled trials

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 87 publications
(156 reference statements)
3
36
0
Order By: Relevance
“…Following the proposal by Wang et al ( 2020a ), there is a need for online mental health training for the professionals. Two metanalysis carried out before the COVID showed that online psychological interventions showed effect in reducing depressive symptoms in non-depressed population (Rigabert et al, 2020 ) and in reducing symptoms of anxiety, distress and depression in chronic health populations (White et al, 2020 ). In this sense, online psychological treatments should be improved in order to respond the need for treatment after confinement periods.…”
Section: Discussionmentioning
confidence: 99%
“…Following the proposal by Wang et al ( 2020a ), there is a need for online mental health training for the professionals. Two metanalysis carried out before the COVID showed that online psychological interventions showed effect in reducing depressive symptoms in non-depressed population (Rigabert et al, 2020 ) and in reducing symptoms of anxiety, distress and depression in chronic health populations (White et al, 2020 ). In this sense, online psychological treatments should be improved in order to respond the need for treatment after confinement periods.…”
Section: Discussionmentioning
confidence: 99%
“…Internet- and mobile-based interventions (IMI) as one kind of low intensity intervention offer anonymity, temporal and local independency, easy accessibility, and scalability 27 30 and are thus suggested to hold potential in overcoming structural healthcare barriers 31 , 32 . Despite reports of lower treatment completion rates 33 , IMI have been proven effective in preventing and treating mental disorders 34 38 . However, they were mostly developed for and evaluated in majority populations from high-income countries, and were found to be less effective for people with a differing cultural or ethnic background 39 .…”
Section: Introductionmentioning
confidence: 99%
“…This is contradicted by other reviews, which found only small effects in preventing depression (e.g. Rigabert et al, 2020). However, a recent review showed that telehealth applications and Internet-based therapy are useful tools in treating social anxiety (Andersson et al, 2014), post-traumatic stress disorder (PTSD) (Kuhn & Owen, 2020), and first RCTs show promising results of Internet-based…”
Section: Internet-based Therapymentioning
confidence: 94%